NOVEL CHARLOTTE KARYA DAVID FOENKINOS: SEBUAH NARASI TENTANG DISKRIMINASI, RASISME, DAN HOLOCAUST - Tania Intan (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
The Nazi ruling since 1933 made no secret of his dislike of Jews. Adolf Hitler even declared that